Understanding the willingness of healthcare workers to treat viral infected patients in Saudi Arabia: evidence from post-COVID-19 pandemic - Alotaibi, Abdulhadi Sharhan (Frontiers in Sociology, 2025)
During the recent COVID-19 pandemic, healthcare workers played an essential role in saving millions of lives and stopping the spread of the virus worldwide. This study investigates the impact of perceived behavioral control, attitudes, subjective norms, and emotion-focused coping on willingness to treat viral-infected patients in Saudi Arabia. However, the theory of planned behavior was extended by including emotion-focused coping. Data were collected from 283 male and female healthcare workers from public, private, and semi-government hospitals. “Structural Equation Modeling” (SEM) was applied to test the hypothetical relationship using SmartPLS software. Overall, the findings indicate that healthcare workers perceived behavioral control, subjective norms, and emotion-focused coping significantly impact healthcare workers’ willingness to treat viral-infected patients. In contrast, attitudes showed a negative effect. In addition, emotion-focused coping mediates the relationship between perceived behavioral control, subjective norms, and willingness to treat viral-infected patients; emotion-focused coping does not mediate the relationship between attitudes and willingness to treat viral-infected patients. Overall, findings suggested that healthcare workers showed positive perceived behavioral control, subjective norms, and emotion-focused coping toward viral-infected patients. On the other hand, due to the novelty of the viral-infected viruses, attitudes of healthcare workers toward willingness to treat viral-infected patients shows that healthcare workers feel stressed and scared to treat viral-infected patients.